Emergency Department Care of Young Children at Risk for Traumatic Brain Injury: What Are We Doing and Do Parents Understand?. Issue 7 (July 2019) - Reilly, Caroline; Zhang, Nanhua; Babcock, Lynn; Wade, Shari L.; Rhine, Tara
Abstract : Objectives: The aims of the study were to describe emergency department (ED) management of young children with head injury and to assess parental comfort level and perceptions of ED care. Methods: This was a prospective observational study of children younger than 5 years who presented to a pediatric ED after head injury. Children were eligible if clinical observation was an appropriate ED management option per the Pediatric Emergency Care Academic Research Network's neuroimaging clinical decision rule. Demographics, injury variables, and ED clinician surveys explaining the care provided were collected at time of study enrollment. Parents were subsequently contacted to assess understanding of ED management and comfort with care. Results: One hundred four children were enrolled with a mean (standard deviation) age of 1.19 (1.34) years. Thirty (29%) had emergent neuroimaging and 59 (57%) were placed into a period of observation per clinician report. A total of 37 children received a head computed tomography, of which 21 (57%) were normal. Eighty-four parents (81%) completed the phone follow-up. Of these children, there was a significant difference between whether parents and clinicians reported that the child had been clinically observed in the ED ( P < 0.0001). Parents of children who did not receive a head CT were more likely to be uncomfortable with the decision to obtain neuroimaging compared with those who did receive a head CT ( P = 0.003). Conclusions: Parents are not always comfortable with the medical care practices provided and are often unaware of clinical observation when it does occur. Better parent-clinician communication could improve parental understanding and reduce overall discomfort.